Accounting Research in Abacus, A&F, AAR, and AJM from 2008–2015: A Review and Research Agenda. (10th April 2017) - Linnenluecke, Martina K.; Birt, Jacqueline; Chen, Xiaoyan; Ling, Xin; Smith, Tom
Abstract : This paper uses bibliographic mapping techniques to map the research conversation in four Pacific Basin accounting journals listed on the Social Sciences Citation Index ( Abacus, Accounting and Finance, Australian Accounting Review, and the Australian Journal of Management ). We identify the main research streams in these journals as Accounting Standards, Environmental Accounting, Earnings Management, Disclosure, Conservatism, Auditing, Impairment, Cost of Capital, and Corporate Governance. We critically review each research stream, identify emerging research trends, and suggest an agenda for future research on accounting in the Pacific Basin.